Nigeria's Legal Regulatory Framework for Ensuring a Credible 2023 Election - Nabiebu, Miebaka (International Journal of Law and Society, 2022)
Since independence, the Nigerian electoral process has been plagued with spiralling anomalies, including worsening violence, intimidation, death and fraud. This has jeopardized Nigeria's socio-economic, political and national security and eroded confidence in the democratic process as well as increased election season security concerns. For elections to be credible, the competition must be fair, which requires impartial process management. So, despite the recently revised Electoral Act and other related laws that could help Nigeria realize its potential for credible elections. This work argues that the legal framework still has several components that must be studied or introduced to improve electoral processes. The method used is qualitative with a case study approach and empirical juridical. The results of this study propose that Article 225 of the Constitution be amended to eliminate the requirement for cash given to political parties from outside Nigeria to be transferred to INEC; otherwise, the donation must be notified to INEC and made public. The constitution should be modified to establish an Election Offenses Commission or Court to try and punish individuals (INEC officers, candidates and voters) who violate articles 114–128 of the new law. Section 29(5) of the Elections Act should be amended to allow the Federal Capital Territory and the High Court of Abuja State to hear and resolve pre-election disputes. In addition, instead of focusing on technical matters, the trial for the regional election application should focus more on the substance of the application and the facts of the case.